Longitudinal Electromagnetic Waves? The Monstein-Wesley Experiment Reconstructed - Butterworth, Edward J.; Allison, Charles B.; Cavazos, Daniel; Mullen, Frank M. (Journal of Scientific Exploration, 2013)
We repeat the experiment reported in a controversial publication of Monstein and Wesley (MW), in which they claimed to have detected longitudinal electromagnetic (EM) waves in free space, a phenomenon incompatible with Maxwell’s equations. While we are convinced that Maxwell’s equations are valid and that longitudinal EM waves do not exist, we recognized that the radiation pattern observed in the MW experiment was itself interesting, while noting that no one had actually repeated MW’s experiments. Therefore we constructed a duplicate of MW’s apparatus and ran their experiments along with some additional ones. We intended both to test whether MW’s results could be duplicated, and to distinguish between their theoretical model and that of a critical article published by Rębilas proposing ground plasma currents as the true cause of the waves observed by MW. We also determined the field pattern of the ball antenna experimentally. Our experimental results actually resemble MW’s theoretical pattern more closely than did their own experiment, an interesting result considering that MW’s theory is almost universally considered incorrect. However, our experimental results were not compatible with Rębilas’ (very plausible) theoretical explanation. Thus we dispute MW’s claim on theoretical grounds, and Rębilas’ ground plasma currents on experimental grounds. We conclude that a yet-unidentified mechanism must be producing the observed results.